Evaluation Hormonal State in Iraqi Infertility Females Under In-Vitro Fertilization Program - Zainab Sabah Hassab; Bushra J. Al-Musawi; Asmaa M. Salih Almohaidi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Uniqueness of the current study at first time in Iraq specially, across the comparison theclinical parameters among Iraqi infertility females according the IVF program outcome: failures and successimplantation. While, aspect were neglected in IVF field. Also, to difficulty of some parameters comparingwith control.Methods: This study done during (December 2019 to November 2020) on Iraqi infertile females with agerange (19 – 45)ys. It included the two groups: success implantation and failure implantation females.Result: The current study revealed to that , secondary infertility is a good marker in implantation successprediction. Central circumference increasing has been associated with implantation failure (P<0.05). Whenhormonal profile comparison among two groups. Failure implantation females have non-significant increasingin basic prolactin values. Also, E2, progesterone and LH values were higher significantly(P>0.001), amongsuccess implantation. The hCG values were highly significant in failure implantation (P>0.001). MII oocytesand G2 embryos were highly significant in success implantation. Our result support that no. of embryocells have positive impact on IVF outcome. The S. TC and TG were significant increasing among failureimplantation.